Computer numerical control printed circuit board drilling machine. / Mohd Hisham Hj. Ibrahim and Norlela Mustaffa - Ibrahim, Mohd Hisham; Mustaffa, Norlela (Faculty of Mechanical Engineering, 1997)
Computer Numerical Control has been found to be extensively used in the manufacturing industry in view of the programmability and accuracy it provides. Printed Circuit Board drilling is an ideal application for demonstrating the Computer Numerical Control concept. Further mass produced and high accurate components for linear motion such as recirculating ball screws, linear bearings and Linear Motion elements are readily available at low cost. Hence a Printed Circuit Board drilling machine using the CNC principles and above mentioned Linear Motion elements, has been conceptually designed. The mechanical part of the machine was planned for fabrication, but the non availability in time, has forced us to demonstrate a small scale model utilising the components already available in CADEM Center.